MEDIA AJAR RAGAM HIAS ECOPRINT TEKNIK POUNDING PADA TAS JINJING - Nufadillah, Nurfadillah; Ahmad, Abd. Aziz; Aswar, Aswar (JURNAL IMAJINASI, 2025)
This research is research and development (R&D) which refers to the 4D development model according to Thiagarajan (1974). This research aims to develop teaching media for ecoprint decoration using pounding techniques in class VII of SMP Negeri 5 Pallangga based on valid presentations. This development research was carried out through three stages, namely define, design and development. Data collection techniques include observation, validation from material and media experts and documentation. From the data collected based on validation from material experts and media experts, it was then converted using the Benchmark Reference Approach (PAP) referring to Widoyoko (2009). The results of the research achieved after analysis are: 1) teaching materials for decorative ecoprint pounding techniques with an average assessment score by material experts from the aspects assessed, namely content and objective aspects, instructional quality is 4.52, category (very good), and declared suitable for use with revisions. 2) Research by media experts from the technical quality aspect obtained an X score (average score obtained) of 4.6, category (very good), and was declared suitable for use with revision. Based on this data, it can be concluded that the teaching media for ecoprint decorative pounding techniques on tote bags is suitable for use as a support for learning activities at SMP Negeri 5 Pallangga.